Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries - Nagy, Zoltán (2024)
Today's economic problems clearly demonstrate the importance of economic governance in the European Union, which must respond to social and economic events in a relevant and timely manner. In addition to financial sovereignty, international expectations and EU standards must also be met. The resource requirements arising in the EU budget cycle would increase the common budget, but this is only possible if additional resources are withdrawn from Member States' budgets, which affects the autonomy of Member States' budgetary management. In addition to the common monetary policy and the introduction of the euro, the regulation of non-participating Member States also raises relevant issues.The aim of this book is to present and analyze the conflicts arising from European Union and Member State regulations. The coordination of EU and Member State regulations is particularly important, as there are issues that can only be addressed at the integration level, and Member States are not always able to respond to them on their own, but these individual regulatory solutions can also serve as guidelines for other Member States or the EU. Member States retain their budgetary independence and responsibility, but at the same time they must comply with European Union criteria. All these issues highlight the relevance of this book.In addition to EU central regulation, the research focuses on individual Central European countries. The book aims to provide a comprehensive overview of economic governance, analyzing current regulatory issues. The book is divided into two main parts, fiscal policy and monetary policy, which present the regulatory problems of the EU and individual member states. This is such a broad area of regulation that the research only highlights the most significant areas. The section on fiscal policy consists of three subsections: public finances, state aid, and taxation. The second major part of the research deals with monetary policy, presenting both the monetary policy and institutions of the EU and individual member states.